Analysis of feasibility and safety of laparoscopic complete mesocolic excision with central vascular ligation for right-sided colon cancer: A single centre experience (Annals of Medical Research, 2021)
Aim: Colectomies performed according to complete mesocolic excision (CME) principles have demonstrated an improvement in the quality of surgical specimen and a potential improvement of long-term results. The procedure is technically challenging and has a risk of serious complications, especially when performed laparoscopically. We here aimed to analyze our short-term results in relation to laparoscopic CME right hemicolectomy carried out for right-sided colon cancers. Material and Methods: Demographic data and preoperative, perioperative and postoperative parameters of twenty-three patients who underwent laparoscopic CME between January 2017 and January 2019 in our clinic for right-sided colon adenocarcinoma were retrospectively analysed.Results: There were 23 patients in our study and the mean (SD) age was 61.9±14.8. In the present series, 30% of patients were ≥70 years old, and three were ≥80 years old. Four patients were ASA class 3. Fifty-two percent of patients had comorbidities, and two had different system malignancies in their medical history. While the mean (SD) body mass index (BMI) was 25±4.3, BMI of 4 patients were over 30. Six of patients had a history of previous abdominal surgery. No perioperative mortality was observed. Thirteen percent of the patients developed wound site infection. Anastomotic leakage occurred in 2 cases, and one of them underwent reoperation. The mean (SD) operation time was 168±33 min. Good quality specimens were obtained with a mean (SD) length of 34.2±9.7 cm, a proximal margin of 14±8.2 cm and a distal margin of 16.6±8.9 cm. The mean (SD) number of harvested lymph nodes was 31.9±7.7. The radial surgical margin of all specimens was negative. The mean (SD) postoperative hospital stay was 7.2±2.8 days.Conclusion: We believe that our CME technique performed by laparoscopic method for right-sided colon cancers is safe and applicable, and allows obtaining good quality specimens when evaluating the short-term results. However, there is still a need for randomized controlled trials to evaluate the contribution to survival.
Keywords: Colon cancer; complete mesocolic excision; laparoscopy; right hemicolectomy